Risiko Produksi dan Pendapatan Usahatani Padi di Desa Simbolon Purba Kecamatan Palipi Kabupaten Samosir Provinsi Sumatra Utara - RANDA FAUSTIN SIMARMATA; I WAYAN WIDYANTARA; I DEWA GEDE AGUNG (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2021)
Risk Of Rice Farming Production And Income In Simbolon Purba Village Palipi District Samosir Regency North Sumatra Province Rice farming on Samosir Island has the potential to become food self-sufficiency. However, agriculture in the village of Simbolon Purba only produces in one growing season, which is in the rainy season and automatically fails to harvest during the dry season. This is because agriculture in the village of Simbolon Purba only relies on rainwater for irrigating paddy fields. This study aims to determine how the risk of production and the income earned in rice farming in the Village of Simbolon Purba, Palipi Sub-District. The study was conducted in the Village of Simbolon Purba, Palipi Sub-District, Samosir Regency, North Sumatra Province. Sampling was conducted by taking data from the village office and the number of respondents taken is as many as 50 rice farmers who use rain-fed irrigation and sharecropping. The data used in this study are primary and secondary data. Data processing starts from analyzing risk and proceed with revenue analysis. In calculating the risk, the standard deviation, variance and coefficient of variation are calculated beforehand, while for the calculation of income, the revenue and costs are calculated beforehand to get the income. The average grain production at the study site was 5,910.2 kg / hectare with a coefficient of variation of 0.25 so that the risk of rice farming production at the study site was not critical. The average income of rice farming in Simbolon Purba Village, Palipi Sub-District is Rp. 20.396.634/ha/MT Planting Season with an R/C ratio of 2,14, which means the farm income of the respondent farmers, is efficient. The government needs to provide financial assistance for irrigation so farmers can increase production in two growing seasons and at the same time increase income.